Drug Therapy For Mental Disorders In Psychotropic Law And Islamic Legal Perspectives - Rizka, Rizka; Sari, Septiana Novita; Nurhayati, Nunik; Lyandovy, Vanka (JUSTISI, 2024)
Problems with mental and physical health often occur together. Various conditions of a person’s mental health are referred to as mental illnesses, also known as mental health disorders. Mood, thingking, and behavior are usually affected by these disorders. Therapy has the potential to treat some mental illnesses. However, the are times when therapy alone is insufficient, thus requiring medical assistance. Psychotropic medications can be prescribed by doctors based on the patient’s mental state. This study used a normative strategy. Descriptive research is being conducted. According to the study's findings, patients may safely use psychiatric medications for medical purposes under the watchful eye of the Minister of Health so long as they follow their doctors' orders. In the event of psychotropic abuse will cause sanctions or penalties for psychotropic abusers specifically regulated in the Psychotropic Act, and for psychotropic addicts can undergo medical rehabilitation dan social rehabilitation in accordance with the Psychotropic Act No. 5 off 1997 the use of psychotropic drugs in the view Islamic law if halal goods do not exist or can not be found for use in health services, then it is permissible to use pychotropic drugs for health services Keywords: Drug Use; Pyscotropic Drug; Mental Disorders.